2019
DOI: 10.1093/cercor/bhz027
|View full text |Cite
|
Sign up to set email alerts
|

Hemisphere and Gender Differences in the Rich-Club Organization of Structural Networks

Abstract: Structural and functional differences in brain hemispheric asymmetry have been well documented between female and male adults. However, potential differences in the connectivity patterns of the rich-club organization of hemispheric structural networks in females and males remain to be determined. In this study, diffusion tensor imaging was used to construct hemispheric structural networks in healthy subjects, and graph theoretical analysis approaches were applied to quantify hemisphere and gender differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 80 publications
7
41
1
1
Order By: Relevance
“…The preprocessing steps used were as previously described (Bai et al, 2012;Wang X.N. et al, 2016) and were performed using PANDA software as follows: (Ostrom et al, 2014) format conversion of original data (DICOM); (Raysi Dehcordi et al, 2013) the extraction of brain tissue and structure; (Fornito et al, 2013) realignment; (Hart et al, 2016) Eddy current and motion artifact correction of DTI data by applying an affine alignment of each diffusion-weighted image to the b0 image; (Wang et al, 2019) fractional anisotropy (FA) calculation; (Yan et al, 2018) diffusion tensor tractography; and (Iturria-Medina et al, 2011) conduct of tractography to produce 3D streamlines representing fiber tract connectivity (Mori et al, 1999).…”
Section: Preprocessing Of Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…The preprocessing steps used were as previously described (Bai et al, 2012;Wang X.N. et al, 2016) and were performed using PANDA software as follows: (Ostrom et al, 2014) format conversion of original data (DICOM); (Raysi Dehcordi et al, 2013) the extraction of brain tissue and structure; (Fornito et al, 2013) realignment; (Hart et al, 2016) Eddy current and motion artifact correction of DTI data by applying an affine alignment of each diffusion-weighted image to the b0 image; (Wang et al, 2019) fractional anisotropy (FA) calculation; (Yan et al, 2018) diffusion tensor tractography; and (Iturria-Medina et al, 2011) conduct of tractography to produce 3D streamlines representing fiber tract connectivity (Mori et al, 1999).…”
Section: Preprocessing Of Imagesmentioning
confidence: 99%
“…The development of complex network analysis using graph theory (i.e., connectome) in the brain offers the potential to identify the impacts of focal and diffuse pathologies in glioma patients (Fornito et al, 2013;Hart et al, 2016), such as rich-club organization (Yan et al, 2018;Wang et al, 2019), small-world characteristics (Iturria-Medina et al, 2011;Yan et al, 2018), betweenness (Iturria-Medina et al, 2011), and global and local network efficiency (Iturria-Medina et al, 2011;Shu et al, 2018). Recent studies have suggested that the human brain shares the same key organizational principles as common, natural, and manmade systems, that is to say, that the human brain is thought to be a network of unceasing communication (Hart et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The tractography was terminated when it reached a voxel with an FA value less than 0.1 or when the angle was greater than 35 • . Based on the reconstructed fiber tracts, the WM connection between a pair of nodes was adopted if the fiber number (FN) was larger than 3 (Shu et al, 2011;Li et al, 2018;Wang et al, 2019). We selected the threshold value for the FN > 3 was to reduce pseudo-connections due to possible noise effects on the whole-brain WM tractography (Sun et al, 2015).…”
Section: Data Preprocessing and Network Constructionmentioning
confidence: 99%
“…The node of structural network was defined as one region of the normalized AAL atlas. The weights of the structural network was defined the mean FA values of the connected fibers between 2 regions (Li et al, 2018;Yan et al, 2018;Wang et al, 2019). The reason for choosing FA is that it is an important indicator commonly used to examine the microstructure aspects of brain WM connections (Cui et al, 2013).…”
Section: Data Preprocessing and Network Constructionmentioning
confidence: 99%
See 1 more Smart Citation